2018
DOI: 10.1038/s42255-018-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between hormone-sensitive lipase and ChREBP in fat cells controls insulin sensitivity

Abstract: Impaired adipose tissue insulin signaling is a critical feature of insulin resistance. Here we identify a pathway linking the lipolytic enzyme, hormone-sensitive lipase (HSL), to insulin action via the glucose-responsive transcription factor ChREBP and its target, the fatty acid (FA) elongase, ELOVL6. Genetic inhibition of HSL in human adipocytes and mouse adipose tissue results in enhanced insulin sensitivity and induction of ELOVL6. ELOVL6 promotes an increase in phospholipid (PL) oleic acid which modifies p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 62 publications
2
44
0
1
Order By: Relevance
“…40,41 Palmitate is also a precursor of ceramides and other lipotoxic lipids. 42 Excess fructose is only in part used for DNL and can also be metabolised as uric acid through the purine cycle ( Fig. 2).…”
Section: Hepatic Insulin Resistance and Risk Of Type 2 Diabetesmentioning
confidence: 99%
“…40,41 Palmitate is also a precursor of ceramides and other lipotoxic lipids. 42 Excess fructose is only in part used for DNL and can also be metabolised as uric acid through the purine cycle ( Fig. 2).…”
Section: Hepatic Insulin Resistance and Risk Of Type 2 Diabetesmentioning
confidence: 99%
“…Thereby, HSL retains ChREBP in the cytoplasm, preventing its nuclear translocation and subsequent transcriptional induction of target genes such as the FA elongase ELOVL6, an enzyme catalyzing the elongation of palmitic acid to stearic acid, which can be further desaturated into oleic acid. By contrast, the partial inhibition of HSL, which was shown to improve insulin sensitivity in murine AT and human adipocytes [167,168], increases ELOVL6 expression. As a consequence, increased amounts of oleic acid are incorporated into phospholipids.…”
Section: Carbohydrate Response Element Binding Protein (Chrebp)mentioning
confidence: 94%
“…In humans, the expression of ChREBP and adipose DNL are positively associated with insulin sensitivity [165,166]. Recently, an exciting study demonstrated a direct interaction between HSL and ChREBP regulating insulin signaling in white adipocytes [167]. Thereby, HSL retains ChREBP in the cytoplasm, preventing its nuclear translocation and subsequent transcriptional induction of target genes such as the FA elongase ELOVL6, an enzyme catalyzing the elongation of palmitic acid to stearic acid, which can be further desaturated into oleic acid.…”
Section: Carbohydrate Response Element Binding Protein (Chrebp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Néanmoins, les taux circulants d'acides gras étant inchangés chez ces animaux, les mécanismes impliqués dans ces effets bénéfiques restaient incompris. Dans une étude récemment publiée dans la revue Nature Metabolism, nous montrons qu'une invalidation partielle de la LHS dans des adipocytes humains en culture favorise l'entrée du glucose dans la cellule ainsi que son utilisation pour la synthèse d'acides gras (lipogenèse de novo), et améliore la transmission du signal insulinique [8]. En utilisant des inhibiteurs pharmacologiques des enzymes de la lipogenèse de novo, nous avons constaté que l'activation de cette voie est essentielle aux effets bénéfiques de l'invalidation de la LHS sur la sensibilité à l'insuline.…”
Section: Relation Entre La Lipase Hormonosensible Adipocytaire Et La unclassified